Dos síntomas y una causa: Flujos de capitales, precios de los commodities y determinantes globales - Diego Bastourre; Jorge Carrera; Javier Ibarlucia; Mariano Sardi (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2012)
– This paper presents and evaluates the hypothesis that emerging countries specialized in commodity production are prone to experience non orthogonal commercial and financial shocks. Specifically, we investigate a set of global macroeconomic variables that, in principle, could simultaneously determine in opposite direction commodity prices and bonds spreads in commodity-exporting emerging economies. Employing common factors techniques and pairwise correlation analysis we find a strong negative correlation between commodity prices and emerging market spreads. Moreover, the empirical FAVAR (Factor Augmented VAR) model developed to test our main hypothesis confirms that this negative association pattern is not only explained by the fact that commodity prices are one of the most relevant fundamentals of bond spreads of commodity exporters. In particular, we find that reductions in international interest rates and global risk appetite; rises in quantitative global liquidity measures and equity returns; and US dollar depreciations, tend to diminish spreads of emerging economies and strengthen commodity prices at the same time. These results are relevant in order to improve our knowledge regarding the reasons behind some typical characteristics of emerging commodity producers, such as their tendency to experience high levels of macroeconomic volatility and procyclicality, or their propensity to be affected from exchange rate overshooting, external crisis and sudden stops. Concerning policy lessons, a mayor conclusion is the complexity of the task of disentangle challenges coming from financial openness and structural considerations in emerging economies, such as the lack of diversification of the productive structure or the difficulties of a grow strategy solely based on natural recourses. It would be profitable to internalize the connection between these two key variables in formulating and conducting economic policy.
Keywords: F32; F42; O13; 330; commodity prices; emerging economies; financial flows; market spreads